Modelo multicritério de processo de desenvolvimento de produtos para cadeia de suprimentos automotiva fundamentado nos requisitos da norma ISO TS 16949 - Dzulinski, Ana Caroline (2016)
In order to conduction of this research has identified the following research gap: a model of Product Development Process (PDP) directed to parts suppliers, which includes in its activities the requirements of ISO TS 16949 standard. Thus, the defined objective was to construct of a PDP model to include in its activities the requirements of this standard. The methodology used to achieve the proposed objective consists of: bibliographical research based on the systematic review method, the PDP model proposition directed to automotive industry suppliers with purely theoretical basis, the proposed model analysis through questionnaires addressed to stakeholders (suppliers and manufacturers ), processing of data seeking ordination of model activities due to the importance given by the respondents (using the multicriteria method ELECTRE II), and the adequacy of the initial model according to the data obtained from questionnaires. The opinions of 52 suppliers to the automotive industry, and 2 assemblers have been raised that guided the structure of the resulting final model (called Shared Development Process Products - SDPP) consists of the following stages of development: Opportunity Identification, Planning, Tryout, Continuous Production and Post-Production. For each phase were obtained orders of the activities due to the flow of execution, and including, the order of importance of each activity within their respective PDP phase. For each activity of the model were given the numbers reference the requirements of ISO TS standard 16949 relating to the activities, so that in the PDP course are explicit requirements of the standard that must be met, or evaluated, and at what time. As future research opportunities were identified: Obtaining a greater number of opinions on the activities of the PDP segment, both suppliers and manufacturers; applying the model in development processes shared between manufacturers and suppliers to test and improve the structure of the PDCP model; studies on the differences between manufacturers and suppliers in the shared development; PDP studies to include in their development stages to direct relation to the development of the product manufacturing process and the use of other mathematical models to compare orders of importance of the activities proposed in the model.